What is appropriate surveillance for metal-on-metal hip arthroplasty patients?: A clinical update - Matharu, G; Judge, A; Eskelinen, A; Murray, D; Pandit, H (Taylor and Francis, 2017)
The unexpected high revision rates of large-diameter (femoral head sizes of 36 mm or greater) metal-on-metal hip arthroplasties (MoMHAs) have led worldwide regulatory authorities recommending regular surveillance, even for asymptomatic individuals. However these recommendations are not evidence-based and very costly. As the evidence base is evolving and many patients will undergo regular investigation over future years it is important to provide an update about the investigation and management of MoMHA patients. This article is the first of two, which considers the various investigative modalities used during surveillance, with specific focus on blood metal ion sampling and cross-sectional imaging. No single investigation can universally be used during MoMHA patient surveillance. Recent studies have now provided important information about interpreting blood metal ions (effective at identifying patients at low risk of problems), clarifying the roles of cross- sectional imaging (reserve combined ultrasound and MARS-MRI for complex cases), and providing parameters to safely exclude many asymptomatic patients from regular surveillance. This information will be useful when designing future surveillance protocols for MoMHA patients.